The Effect Of Poverty Rate, Unemployment Rate, And Inflation On The Human Development Index In North Sumatra Province - Kusuma Wardhani; Lia Nazliana Nasution; Rahmad Sembiring (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the effects of poverty, unemployment, and inflation on the Human Development Index (HDI) in North Sumatra Province during the period 2019–2024. The study employs a quantitative approach using secondary data obtained from official publications of Statistics Indonesia, which are empirically analyzed to examine the relationships among variables. The findings indicate that increases in poverty and unemployment negatively affect the quality of human development through limited access to education, healthcare, and a decent standard of living, while inflation weakens purchasing power and hampers improvements in social welfare. Simultaneously, these three variables contribute substantially to variations in the HDI in North Sumatra, highlighting the importance of social and economic stability in supporting human development. This study is limited by the use of a relatively narrow set of macroeconomic variables; therefore, future research is recommended to incorporate public policy factors and regional inequality to provide a more comprehensive understanding